Perbaikan Citra Noise dengan Menggunakan Algoritma World Cup Optimization - Elsa Laurika (STMIK Budi Darma, 2022)
At this time the use of computer technology has grown rapidly and in society. Most people use it not only for commercial purposes, but also to get disease detection information quickly and efficiently with computer-based applications. The world cup optimization method aims to reduce noise by determining the kernel matrix and works by replacing the intensity value of each input image pixel with the average of the kernel weighted value for each neighboring pixel and the pixel itself. In the process of reducing the kernel size noise greatly affects the image quality results. This research has produced an application program to reduce noise with world cup optimization. The test image used in this study uses a color image. The image is input and displayed on the program